The Influence of Online Gambling Advertisements on Student Consumptive Behavior: An Islamic Economic Perspective - Ahmad, Alifah Azizah; Khairunnisa, Daniswara; Anwar, Devi Kurnia; Nurzamiyanti, Ghevira; Pebriyanti, Jovani Shinta; Supriyadi, Tedi (Al-Sharf: Jurnal Ekonomi Islam, 2025)
This study aims to analyze the influence of online gambling advertisements on students' consumptive behavior from the perspective of Islamic economics. Using a descriptive qualitative approach, the study finds that exposure to online gambling ads on digital platforms encourages students to engage in gambling practices and excessive consumption patterns. The impact is exacerbated by low levels of Islamic financial literacy and weak self-control. From an Islamic economic standpoint, online gambling is categorized as maisir a prohibited activity due to its speculative and non-productive nature. The study also highlights the crucial role of families, campuses, and society in preventing students from falling into consumptive lifestyles and online gambling. Therefore, integrating Islamic financial literacy emerges as a strategic solution to protect students from the negative impact of gambling advertisements.